2020
DOI: 10.1186/s12977-020-00537-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the amino-terminal sequence on the structure and function of HIV integrase

Abstract: Background: Antiretroviral therapy (ART) can mitigate the morbidity and mortality caused by the human immunodeficiency virus (HIV). Successful development of ART can be accelerated by accurate structural and biochemical data on targets and their responses to inhibitors. One important ART target, HIV integrase (IN), has historically been studied in vitro in a modified form adapted to bacterial overexpression, with a methionine or a longer fusion protein sequence at the N-terminus. In contrast, IN present in vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 94 publications
(191 reference statements)
0
8
0
Order By: Relevance
“…IN (NL4-3) constructs were expressed and purified as described previously [10,12,101,102]. Individual IN domains (CCD F185K [11], CTD(220-271), CTD(220-270) L242A [52], and CTD (220-288)) were inserted into an expression vector containing an N-terminal His7-Flag-SUMO tag [103]. Proteins were purified with nickel-nitriloacetic acid resin and subjected to a second nickel-nitriloacetic column after fusion proteins were liberated by cleavage with Ulp1 protease (Thermofisher Scientific).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…IN (NL4-3) constructs were expressed and purified as described previously [10,12,101,102]. Individual IN domains (CCD F185K [11], CTD(220-271), CTD(220-270) L242A [52], and CTD (220-288)) were inserted into an expression vector containing an N-terminal His7-Flag-SUMO tag [103]. Proteins were purified with nickel-nitriloacetic acid resin and subjected to a second nickel-nitriloacetic column after fusion proteins were liberated by cleavage with Ulp1 protease (Thermofisher Scientific).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…IN (NL4-3) constructs were expressed and purif ied as described previously (10,12,57,58). Individual IN domains (CCD and CTD) were inserted into an expression vector containing an N-terminal His7-Flag-SUMO tag (59). Proteins were purif ied with nickel-nitriloacetic acid resin and subjected to a second nickel-nitriloacetic column af ter f usion proteins were liberated by cleavage with Ulp1 protease (Thermof isher Scientif ic).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore compared the biophysical properties and activity of HIV-1 intasomes assembled with Sso7d-IN and wild-type IN and devised a strategy to obtain cryo-EM structures of wild-type HIV-1 intasomes. Since it has been reported that the amino-terminal sequence of HIV-1 integrase can influence the oligomerization and function of IN, 11 we also modified the expression construct so that the protein has the native phenylalanine at the N-terminus, rather the additional four amino acids (GSHM) resulting from cleavage of the His-tag with thrombin.…”
Section: Introductionmentioning
confidence: 99%